CO2 Reforming Characteristics under Visible Light Response of Cr- or Ag-Doped TiO2 Prepared by Sol-Gel and Dip-Coating Process - Akira Nishimura; Go Mitsui; Katsuya Nakamura; Masafumi Hirota; Eric Hu (International Journal of Photoenergy)
A Cr- or Ag-doped TiO2 film was prepared by sol-gel and dip-coating process and used as the photocatalyst for CO2 reforming under the visible light. The ratio of amount of Cr or Ag added to amount of Ti in TiO2 sol solution (R) varied from 0 to 100 wt% or 0 to 50 wt%, respectively. The total layer number of Cr- or Ag-doped TiO2 film (N) coated was changed. The CO2 reforming performance with the Cr- or Ag-doped TiO2 film was tested under a Xe lamp with or without ultraviolet (UV) light. As a result, when N equals to 1, the concentration of CO which was a product from CO2 reforming was maximized in Cr doping case for R = 70 wt% and in Ag doping case for R = 1 wt%, respectively. The best result of concentration of CO = 8306 ppmV, concentration of CH4 = 1367 ppmV, concentration of C2H6 = 1712 ppmV is obtained when 𝑁top=7 with Cr doping in this study.